Kalix River Geochemistry - Conrad, Sarah (Luleå University of Technology, 2024)
This dataset contains element concentrations of quantitative element screenings (ICP-MS, 70+ elements) conducted on filtered water samples and the filtered material (cut-off 0.22 μm) from samples taken in the Kalix River and in the Kalix River Estuary during three sampling campaigns (2013, 2014, and 2016). The purpose of the study was to observe changes in the dissolved and particulate element concentrations during spring flood and along a slowly increasing salinity gradient. This dataset also contains Strontium Isotope data collected in the Kalix River in 1991 and 1992.

Water samples from the Kalix River estuaries were collected during the spring flood in February, March, and April 2014, in May and June 2013, and in May, June, and July 2014. Water samples from the Kalix estuaries were collected from the coastguard vessel KBV005 in May and June 2013. Water samples from all sampling stations were collected at a depth of 0.5, 5, and 10 meters, if they were deep enough. At the sampling in March 2014, samples were collected from the first three stations in the estuaries when they were still covered with ice. In 2014, the tests were carried out through a hole in the ice, drilled with an ice drill, and pumped up from depths of 0.5, 5, and 10 meters.
Water samples from the Kalix River during the spring flood 2016, from March to July. In Kalixälven, at the sampling station Kamlunge, samples were collected from a bridge in the middle of the river.
In 1991 and 1992, samples were taken to detect strontium isotopes.

Dessa datafiler innehåller elementkoncentrationer av kvantitativa elementanalyser (ICP-MS, 70+ element) utförda på filtrerade vattenprover, samt det filtrerade materialet (cut-off 0,22 μm) från prover tagna i Kalixälven och Kalixälvens mynning under tre provtagningskampanjer (2013, 2014, och 2016). Syftet med studien var att observera förändringar i de lösta och partikelformiga elementkoncentrationerna under vårflod och längs en långsamt ökande salthaltsgradient. Denna uppsättning data innehåller även strontiumisotopdata som samlats in i Kalixälven under 1991 och 1992.

Vattenprover togs vid Kalixälvens mynningar under vårfloden i februari, mars och april 2014, i maj och juni 2013, samt i maj, juni och juli 2014. Vattenproverna vid Kalixälvens mynningar togs från kustbevakningsfartyget KBV005 i maj och juni 2013. Samtliga prov togs på 0.5, 5 och 10 meters djup om provtagningsstationerna var tillräckligt djupa. Vid provtagningen i mars 2014 togs prover från de tre första stationerna i mynningarna när de fortfarande var istäckta. Under 2014 genomfördes proverna genom att borra ett hål i isen med en isborr och pumpa upp vattenprov från 0,5, 5 och 10 meters djup.
Vattenprover från Kalixälven under vårfloden 2016, från mars till juli. I Kalixälven, vid provtagningsstationen Kamlunge, togs prover från en bro mitt i ån.
1991 och 1992 togs prover för att påvisa strontiumisotoper.
Kalixälvens geokemi
Keywords: GEOCHEMISTRY; GEOCHEMICAL PROPERTIES; environmental chemistry; miljökemi; chemistry; kemi; environmental chemistry; natural science; environmental chemistry; salinity gradient; salthaltsgradient; Natural Sciences; Naturvetenskap; Chemical Sciences; Kemi; Analytical Chemistry; Analytisk kemi; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Environmental Sciences; Miljövetenskap; Geochemistry; Geokemi; Environment; Miljö